Der Wiener Kunstmarkt der Zwischenkriegszeit - Melichar, Peter (Österreichische Zeitschrift für Geschichtswissenschaften, 2006)
This paper scrutinizes the art market in Vienna between the wars thus empirically analyzing the profiles and problems of this object of research. All those participating in the art market (i.e. artists, collectors, art historians, critics, dealers) are included into the research perspective: It is their very coaction that generates the art market. The problems brought about by classification and categorization (e.g. what is art? what is arts-and-crafts? who is an artist?) along with the divergences in counts (e.g. of artists, of art dealers) they result in are discussed. Among other things the widely-used notion of patron of the arts is critically revised and the issue of the blurring of boundaries between commercial and private actions of the scholars, critics and connoisseurs is raised.